Conocimiento, actitudes y prácticas en casos nuevos de tuberculósis pulmonar con bacilo de Koch positivos bajo tratamiento antifímico zona 7 - Ecuador. - Guzmán Vera, Andrea Elizabeth (2014)
In this paper the relationship, knowledge, attitudes and practices in patients with pulmonary tuberculosis BK + is looking, I raised objectives as: Determine the level of knowledge, attitudes and practices in patients with pulmonary tuberculosis (Bk +) in new cases under treatment antifimic in Ecuador Zone Seven. The methodology used was descriptive, retrospective because they focus on collecting data that specify the knowledge, attitudes and practices in patients with pulmonary tuberculosis (BK +). The universe consisted of all diagnosed cases of pulmonary tuberculosis (BK +) and paid into the program (PCT) during the period 2013. The technique was a structured interview of 20 questions developed based on the study variables, to be applied to patients diagnosed with pulmonary tuberculosis, tabulation and analysis of data was performed using the frequency tables in Excel operational program with the following results: in 2013, the province of El Oro is the most affected with 79%, 4% of patients manifest not know the name of the disease, 8% do not know that it is a contagious disease 11% reveal not take any preventive measures, 47% of patients said they had been afraid to recognize sick, 41% of patients who receive the treatment say it is very long, many tablets and cause discomfort, the same as cause treatment discontinuation, 94% to present their first symptoms came to medical attention. To prevent transmission of TB to 60% use of mask. Upon completion of the research work was thought appropriate to give recommendations for those involved in the problem, so that public health institutions develop programs of information, education, counseling and prevention of pulmonary tuberculosis. Keywords: Pulmonary Tuberculosis, Knowledge, Attitudes, Practices.